The Implementation of the Bengkulu Offering Dance Extracurricular Program in Developing Kinesthetic Intelligence Among Early Childhood Learners at Aisyah 2 Bustanul Athfal Kindergarten, Karang Suci Village - Yunita Dwi Febriyani; Ahmad Suradi; Budrianto Budrianto (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aimed to describe the implementation of the Bengkulu Offering Dance extracurricular activity in developing kinesthetic intelligence among early childhood students at TK Aisyiyah 2 Bustanul Athfal 2, Karang Suci Village. This research employed a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that the Bengkulu Offering Dance extracurricular activity was implemented through several stages, including the introduction of dance movements, practice using counting rhythms, practice with music accompaniment, and evaluation. The dance activity contributed to the development of children's kinesthetic intelligence, as reflected in their ability to control body movements, maintain balance, coordinate movements, understand spatial orientation, and improve self-confidence and cooperation with peers. Although there were some obstacles, such as limited practice space and insufficient parental support, the dance activity was carried out effectively and provided positive benefits for children's development.